Policy Network Analysis and Stakeholder Synergy in Public Policy Implementation in Subang Regency - Rizky Ilhami (Brilliant International Journal Of Management And Tourism, 2025)
Policy networks and synergies among stakeholders are key factors in the effectiveness of public policy formulation and implementation at the local level. This study aims to analyze the structure of policy networks and the level of synergy among actors in public policy in Subang Regency, as well as to identify the obstacles encountered. The study uses a qualitative approach with a descriptive-analytical method. Data were collected through in-depth interviews, observations, and documentation studies of local government, non-governmental organizations (NGOs), the private sector, and the community. The results show that collaboration among actors is still limited, the distribution of resources and influence is uneven, the capacity of non-governmental actors is limited, coordination and communication are less than optimal, and regulatory support that encourages participation is still minimal. This study concludes that strengthening policy networks and synergies between actors through collaborative forums, capacity building, sustainable collaborative mechanisms, regulatory simplification, and shared learning can improve the effectiveness of public policy, strengthen cross-sector collaboration, and support participatory and accountable governance in Subang Regency.